Alterations in white matter integrity in cognitively stable Down syndrome correlate with plasma neurofilament light chain: Evidence of early myelin breakdown. (1st February 2022) - Rosas, H. Diana; Hasimoglu, Yasemin; Mercaldo, Nathaniel; Lai, Florence; Petersen, Melissa; Brickman, Adam M.; Keator, David; Yassa, Michael A.; Lott, Ira T; Silverman, Wayne; Schupf, Nicole; O'Bryant, Sid
Abstract: Background: Alterations in white matter (WM) integrity occur in adults with DS during the early stage of dementia. These changes may be documented by diffusion tensor imaging wherein increases in radial diffusivity (RD), a marker of dysmyelination or myelin breakdown, occur in commissural and limbic pathways in DS. Neurofilament light chain (NfL) is a support protein within large, myelinated axons specifically within the cerebral white matter and is released into blood following axonal damage and is increased in DS. In this study, we evaluated the association between plasma NfL concentrations and RD. Method: Thirty cognitively stable adults with DS from the Alzheimer Disease in Down Syndrome (part of the ABC‐DS) study, (18 M, 12 F: mean age 47.1 years SD 5.2 years), underwent DTI and plasma NfL concentration measurements. Plasma NfL was assayed using the Simoa platform. Diffusion MRI connectometry was conducted using q‐space diffeomorphic reconstruction and a multiple regression model to assess the associations between plasma NfL and white matter radial diffusivity (RD). The Spearman correlation coefficient, and its 95% confidence interval (CI), was used to quantify the monotonic association between plasma NfL and RD. Result: Consistent with our hypothesis, we found positive associations between plasma NfL and RD increases, in several WM higher order association tracts, including the corpus callosum (0.46, 95% CI 0.11‐0.70, p=0.012), the cingulum bundle (L: 0.62, 0.34‐0.80, p<0.001; R: 0.54 0.23‐0.76, p=0.002) and the uncinate fasciculus (L: 0.17, ‐0.20‐0.50, p=0.367; R: 0.51, 0.18‐0.73, p=0.004). Conclusion: Our findings support an important link between alterations in WM myelin integrity, particularly of higher order association areas, and axonal degeneration in cognitively stable adults with Down syndrome. These findings support an important role of WM alterations in adults with DS who are at risk for and who develop AD earlier than in sporadic AD cases. WM might provide an important and novel target for intervention. Additional research is needed to understand the underlying neuropathological processes, including the potential contribution of neuronal dysfunction and/or loss to our findings. Acknowledgements: NIH grant U01AG051412. We are grateful to our participants, families, the agencies serving individuals with ID, and our dedicated staff.